Affective Pathfinding in Video Games - Daszuta, Marcin; Wróbel, Filip; Rynkiewicz, Filip; Szajerman, Dominik; Napieralski, Piotr (Wydawnictwo Politechniki Łódzkiej, 2018)
To allow player submerge in created environment of a video game, agents called Non-Player Characters (NPCs) should act believably. One of the most vital aspect, in case of NPCs is pathfinding. There are a few methods that allow change path finding algorithms to become more human-like. Yet, those are not considering many vital aspects of human decisions regarding path choosing. The main purpose of this paper is to present known approaches and show example of a new approach that wider considers psychological aspects of decision making in case of choosing a path.
Keywords: computer games; pathfinding; AI; artificial intelligence; gry komputerowe; poszukiwanie drogi; sztuczna inteligencja